2018
DOI: 10.1186/s12889-018-5041-5
|View full text |Cite
|
Sign up to set email alerts
|

Dairy product consumption and risk of hip fracture: a systematic review and meta-analysis

Abstract: BackgroundDairy product consumption may affect the risk of hip fracture, but previous studies have reported inconsistent findings. The primary aim of our meta-analysis was to examine and quantify the potential association of dairy product consumption with risk of hip fracture.MethodsWe searched the databases of PubMed and EMBASE for relevant articles from their inception through April 17, 2017. The final analysis included 10 cohort studies and 8 case-control studies. Random-effects models were used to estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
5
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 48 publications
2
59
5
2
Order By: Relevance
“…Biver et al [216] prospectively followed a cohort of 65-yearold healthy Swiss women and showed that age-related Ct bone loss was attenuated at non-bearing bone sites in fermented dairy product consumers, but not in milk consumers, independently of total energy, calcium, and protein intakes. According to a recent study, there was insufficient evidence to deduce the association between milk consumption and risk of hip fracture, which was however reduced by yogurt and cheese consumption [217].…”
Section: Bone Remodeling Osteoporosis and Fracture Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…Biver et al [216] prospectively followed a cohort of 65-yearold healthy Swiss women and showed that age-related Ct bone loss was attenuated at non-bearing bone sites in fermented dairy product consumers, but not in milk consumers, independently of total energy, calcium, and protein intakes. According to a recent study, there was insufficient evidence to deduce the association between milk consumption and risk of hip fracture, which was however reduced by yogurt and cheese consumption [217].…”
Section: Bone Remodeling Osteoporosis and Fracture Riskmentioning
confidence: 99%
“…Until today, no epidemiological study considered the heat processing (pasteurization vs UHT) of milk and did not report on the presence or absence of bioactive milk exosomes and their miR cargo [190,[212][213][214][215][216][217][218][219][220][221][222][223][224][225]. The presence of bioavailable milk exosomes is however of utmost importance to understand the differences in the biological function of pasteurized versus UHT milk on bone homeostasis.…”
Section: Bone Remodeling Osteoporosis and Fracture Riskmentioning
confidence: 99%
“…Of the 19 studies, eight [10,12,[17][18][19][20][21][22] were excluded for reasons including either earlier publications and/or with fewer studies included, limited to a high versus low comparison of intake or reported neutral associations between a dairy product and the health outcome. A summary of the eleven studies [6][7][8][9]11,14,[23][24][25][26] included in the current model is provided in Table 1. Based on our review of the evidence on the beneficial effects of dairy consumption on chronic disease outcomes, inverse associations between dairy consumption and heart disease, type 2 diabetes, colorectal cancer, and hip fractures were identified.…”
Section: Identification Of Health Outcomesmentioning
confidence: 99%
“…The association between yogurt and type 2 diabetes was associated with a 6% reduction in type 2 diabetes for each 50 g/day of consumption [7]. In a meta-analysis by Bian et al [26], the association between dairy consumption and risk of hip fracture was summarized based on nine cohort studies and seven case-control studies. In the analyses limited to cohort studies only, yogurt and cheese were associated with a significant reduced risk of hip fractures based on four data points each when comparing high versus low categories of intake and therefore were included in the current model.…”
Section: Identification Of Health Outcomesmentioning
confidence: 99%
“…Holvik et al 24 found no association between increased milk intake and risk for hip fractures in Norwegian women and men. The most recently published meta-analysis (2018), which included 18 observational studies, showed that higher milk intakes were not associated with fractures in both sexes combined 25. However, it is worth noting that there was a large amount of heterogeneity between studies in terms of reporting milk/dairy intake, number of fractures, use of different confounders for adjustment and fracture ascertainment methods.…”
Section: Introductionmentioning
confidence: 99%